Emotion regulation mediates the relationship between family caregivers’ pain-related beliefs and patients’ coping strategies - Alinajimi, Fatemeh; Deldar, Zoha; Dehghani, Mohsen; Khatibi, Ali (Frontiers in Behavioral Neuroscience, 2023)
Background: In order to tailor more effective interventions and minimize the burden of chronic pain, it is critical to identify the interaction and contribution of social and psychological factors in pain. One of the important psychological factors in pain management is related to the choice of pain coping strategies in chronic pain patients. Social resources, including family caregivers’ pain attitudes-beliefs, can influence pain coping strategies in chronic pain patients. Moreover, one key factor that may intervene in the relationship between caregivers’ pain attitudes-beliefs and the patients’ coping strategies is the emotion regulation strategies. Therefore, the present study aimed to investigate the mediating role of emotion regulation strategies of chronic pain patients and their family caregivers on the association between caregivers’ pain attitudes-beliefs and pain coping strategies of chronic pain patients. Methods: We recruited 200 chronic musculoskeletal pain patients and their family caregivers. Chronic pain patients responded to measures of pain coping and emotion regulation strategies while family caregivers completed questionnaires related to their attitude toward pain and emotion regulation of themselves. Results: There is an association between caregivers’ pain attitudes-beliefs and pain coping strategies in patients with chronic musculoskeletal. Moreover, the structural equation modeling revealed that the emotion regulation of both patients and family caregivers mediate the relationship between the caregivers’ pain attitudes-beliefs and pain coping strategies of patients with chronic musculoskeletal. Conclusions: The social context of pain, including the effect of family caregivers’ responses to the patient’s pain, is a critical pain source that is suggested to affect coping strategies in patients. These findings suggest an association between pain attitudes-beliefs in family caregivers and pain coping strategies in patients. Moreover, these results showed that the emotion regulation of both patients and their family caregivers mediates this association.